PERANCANGAN ALAT UKUR INTENSITAS CAHAYA BERBASIS ARDUINO LEONARDO MENGGUNAKAN SENSOR LDR (Light Dependent Resistor) - Simson Manik; Abdul Muis Muslimin; Aries A. Subgan (FMIPA Universitas Papua, 2020)
Lux meter is a device used to measure the intensity of light in an area. The purpose of this thesis is to design a light intensity measuring device using LDR components as a light sensor, comparing light intensity measuring devices made using LDR sensors and Arduino Leonardo based microcontrollers with standard tools. The data used in this study are primary data. The data obtained is then processed using MS. Excel. The type of light bulbs used are Philips CFL (Philips Essential) lamps, each lamp having a power of 5, 8, 11, 14, 18, 23, 27, 32, 35, and 50 watts with a luxmeter vertical distance of 1, 2 and 3 meters from the lamp. From the results of testing the tools and processing of comparative data between the Lux Meter Standard and the designed Lux ​​Meter obtained as follows: the vertical distance of the tool by 1 meter from the lamp produces an average error difference of 12,571 lx and the percentage of average errors the average is 8.77%, while for the vertical distance of the tool is 2 meters from the lamp the average error difference value is 2,358 lx and the average error percentage is 7.98%, and for the vertical tool distance is 3 meters from the lamp the difference in error value is an average of 0.92 lx and an average error percentage of 5.85%.